(untitled) (Herald of Journalism, 2018)
Civic education and patriotism – a deliberate and systematic activities for the formation of high patriotic consciousness among young people, a sense of loyalty to the Fatherland, readiness to fulfill their civic duty and constitutional duty to protect the interests of the motherland. It is directed at the development of the person having the qualities of a citizen – the patriot of the country and able to successfully fulfill civic duties in peacetime and wartime. The authors attempt to examine the mechanisms of formation and improvement of Kazakhstan’s New patriotism. The article concluded that a significant factor in the formation of the New Kazakhstan patriotism today are information resources, procedural technology PR, documentary and feature films.